(untitled) (Research, Society and Development, 2022)
Objective: To compare the impact on lipid profile (LP) in people starting antiretroviral therapy (ART) before e after the use with efavirenz (EFZ) or dolutegravir (DTG) based regimens. Methods: A prospective cohort study stratified into two groups, the people living with HIV (PLWHIV) who started either DTG or EFV. Dyslipidemia was defined by laboratory criteria in the period from September 2015 to October 2017. Parametric and non-parametric tests and matched pair tests were used, considering p <0.05 statistically significant. Results: Studied 468 individuals stratified into two groups, with (n=180) or without (n=288) records of laboratory tests at time T0 (start of treatment) or at T48 (12 months after the dispensation of antiretroviral drugs. Among these 180, 60 (33.1%) were taking DTG and 113 (62.4%) were taking EFZ. In comparisons of serum PL level (mg/dl), pre and post ART, all values showed an increase and statically significant for HDL (p<0.001). The variation of PL was analyzed, post TARV and in relation to the use of EFV and DTG. In relation to EFZ, there was an increase in the serum level of the whole PL, statically significant for HDL. Regarding DTG, there was increase in serum level only for VLDL which was not statically significant. Conclusion: Comparing the use of DTG with EFV, EFV increased the serum level of TC and fractions, statically significant for HDL. With the use of DTG, there was an increase in serum VLDL level and decrease in HDL-C, without statistical significance.